Administration of oral white oyster mushroom (Pleurotus ostreatus) ethanol extract improved lipid profile as effective as simvastatin in dyslipidemic male wistar rats (Rattus norvegicus) - Nadia Anastasia; I Wayan Weta; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: Dyslipidemia is an abnormality in lipid metabolism characterized by an increase in total cholesterol, LDL, triglyceride, and decrease HDL. Simvastatin is currently a gold standard drug that has side effects, so an alternative therapy that is relatively safe is needed. The white oyster mushroom extract contains bioactive compounds that have the anti-dyslipidemia effect. The purpose of this study was to prove that the administration of oral white oyster mushroom (Pleurotus ostreatus) extract improves lipid profile as effective as simvastatin in dyslipidemic male Wistar rats (Rattus norvegicus). Methods: This study was an experimental study with pretest-posttest control group design by using 12 rats. Rats were induced by dyslipidemic with a high cholesterol diet for 28 days and divided into 2 groups. The control group was fed with standard food and statins of 10 mg/day and the treatment group was fed with a standard diet and white oyster mushroom extract. Results: The results of paired data analysis showed that both simvastatin and white oyster mushroom extract reduced total cholesterol (p<0,001) and (p<0,001), triglycerides (p<0,001) and (p=0,005), LDL (p<0,001) and (p<0,001) and increased HDL (p <0,001) and (p<0,001). Between groups before treatment (pretest) showed no differences levels in total cholesterol, triglyceride, LDL, and HDL. After treatment (posttest), there were also no differences levels between groups in total cholesterol (p=0,097), triglyceride (p=0,160), LDL (p=0,980), and HDL (p-0,452). Conclusion: The administration of oral white oyster mushroom (Pleurotus ostreatus) extract improved lipid profile as effective as simvastatin in dyslipidemic male Wistar rats (Rattus norvegicus).